تنكو محمد حسبي الصديقي وجهوده في تطوير الفقه الأسلامي في أندونيسيا - Muhammad Iqbal Kilwo
Through this research, the researcher studied personal of Tengku Mohammad Hasbi Ash-Shiddieqy and studied his ideas about Fiqh appropriate for Indonesian society and the main causes for this idea. The relationship between this idea and all his public and his efforts in the scientific literature in particular as an integrated unit for the development of Islamic jurisprudence in Indonesia. Either the research methods used by researcher at the completion of this letter are: First: Gather information in need of this research from different sources. Second: The examination of the information on the descriptive approach by combining the deductive and the inductive approach to reach the intended results of this search. And the author found and concluded that, First: Tengku Muhammad Hasbi Al-Shiddiiqiy is a great and eminent Ulama, who has served the Indonesian people through knowledge and his dakwah. Second: Hasbi was a moderate Ulama and not extreme, he holds the Quran and Sunnah. Third: He was in love with each ulama non-absolute reverence any of them. Fourth: He was away from the principle of fanaticism, and hold only on the right. Fifth: He was successful in efforts to expand and renew the Islamic Fiqh in Indonesia by putting a method of ijtihad and some Fiqh legal ruling in accordance with current developments and adopted to solve the various problems arising in the middle of the Indonesian people. Sixth: In this way, Hasbi has been successful in his efforts to state and prove that Islam is a religion that is suitable for all times and places.